2019
DOI: 10.1590/1981-22562019022.180143
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of use of time by family caregivers of elderly persons with dementia

Abstract: Objectives: to describe patterns of use of time in family caregivers of elderly people with dementia, considering the characteristics of the caregivers, the care recipients and the context. Method: Fifty family caregivers of elderly people with intermediate and high levels of physical and cognitive disability participated in an interview about time spent on obligatory care activities over four periods of six hours during a 24-hour period. In addition, a questionnaire about social activities, scales of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
3
1
1
Order By: Relevance
“…5,10,11 Caregivers' average education level was 8.0 years of schooling, results evidenced in national studies. 12,13 However, in an international study carried out in Faro (Portugal) involving 110 informal caregivers for dependent elderly found that most caregivers (67.3%) had four years or less of education, characterizing a low education profile. 14 People with a lower educational level may be susceptible to the caregiver role, as society requires higher educational levels in the formal labor market.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11 Caregivers' average education level was 8.0 years of schooling, results evidenced in national studies. 12,13 However, in an international study carried out in Faro (Portugal) involving 110 informal caregivers for dependent elderly found that most caregivers (67.3%) had four years or less of education, characterizing a low education profile. 14 People with a lower educational level may be susceptible to the caregiver role, as society requires higher educational levels in the formal labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings illustrate the guilt carers feel about taking respite or utilising self-care because of the perception that they should assume all caring responsibilities. Although past research has already suggested that respite from caring is helpful for the carer(Solum Myren et al, 2015;Hajek and Konig, ¨ 2019;Carvalho and Neri, 2019), our findings indicate that time away would be even more helpful if the carer did not also have to struggle with the guilt and resentment that might arise from prioritising one's own self-care.…”
contrasting
confidence: 76%
“…The reorganization of time use by family caregivers and the provision of formal support can reduce the burden of caring and benefit the well-being of caregivers. 31 In the present study, elderly caregivers reported receiving more material/financial support at follow-up compared to baseline. This finding may be related to the increasing age of older care recipients, which may increase dependence on self-care or financially.…”
Section: Discussionmentioning
confidence: 48%